Increasing Sharia Financial Literacy Through Sharia Financial Training and Assistance for Teachers (Universitas Negeri Semarang, 2022)
The Islamic finance industry, in the last ten years, has continued to experience growth. This growth trend is likely to continue considering Indonesia's vast potential. It is coupled with the demographic conditions of Indonesia, where most of the population is Muslim. However, this growth has yet to be maximized, considering that the Islamic banking industry's market share in 2019 was only 5.70%. According to OJK research in 2016, one of the factors for this problem is the low level of Islamic financial literacy in our society, which is only around 8%. So, it is necessary to carry out education so that our Islamic financial literacy increases. One of the strategic steps in the education process is through formal educational institutions, especially secondary education levels, both SMA and SMK. For this reason, so that education goes according to expectations, it is necessary to increase literacy for teachers first. The teacher has a crucial position in the world of education. Excellent Human Resources (HR) for a teacher is an absolute thing in the educational process. It is non-negotiable because it has been mandated in Article 8 of Law No. 14 of 2005 concerning Teachers and Lecturers. So teachers in any field must have sufficient competence. Based on this background, Islamic financial training and assistance are needed to increase Islamic financial literacy for teachers. With this dedication, it is hoped that it can increase public sharia financial literacy through educational institutions. Industri keuangan syariah dalam 10 tahun terakhir terus mengalami pertumbuhan. Namun, pertumbuhan tersebut hingga saat ini dirasa belum maksimal mengingat market share industri perbankan syariah tahun 2019 baru sebesar 5,70%. Menurut penelitian OJK tahun 2016 menujukan salah satu faktor permasalahan tersebut adalah masih rendahnya literasi keuangan syariah masyarakat kita, yakni hanya sekitar 8%. Untuk menanggulangi permasalahan tersebut perlu dilakukannya edukasi agar tingkat literasi keuangan syariah kita meningkat. Salah langkah strategis dalam proses edukasi tersebut adalah melalui lembaga pendidikan formal, terutama jenjang pendidikan menengah baik SMA maupun SMK. Untuk itu agar edukasi tersebut berjalan sesuai dengan harapan, maka diperlukan peningkatan literasi kepada guru-guru terlebih dahulu. Mengingat guru memiliki posisi yang sangat penting dalam dunia pendidikan. Sumber Daya Manusia (SDM) yang unggul seorang guru adalah hal mutlak dalam proses pendidikan. Hal ini tak bisa ditawar karena sudah diamanatkan dalam Pasal 8 Undang-Undang No 14 Tahun 2005 tentang Guru dan Dosen. Sehingga guru bidang apapun harus memiliki kompetensi yang cukup. Berdasarkan latar belakang tersebut maka diperlukan pelatihan dan pendampingan keuangan syariah untuk peningkatan literasi keuangan syariah bagi guru. Dengan adanya pengabdian ini diharapkan dapat meningkatkan literasi keuangan syariah masyarakat melalui lembaga pendidikan.